Supramolecular structure of polypropylene fibers formed with addition of functionalized graphene oxide. Issue 19 (October 2020) - Broda, Jan; Baczek, Marcin; Fabia, Janusz; Fryczkowski, Ryszard
Pimelic acid and calcium hydroxide were used to attach calcium pimelate to the surface of graphene oxide. The additive was mixed with isotactic polypropylene granulate. Neat polypropylene and polypropylene with functionalized graphene oxide was extruded into fibers under laboratory conditions. The gravity spun fibers containing different concentration of the additive and the fibers taken at various velocities were obtained. Morphology and elemental composition of functionalized graphene oxide were studied by means of scanning electron microscopy and energy dispersive X-ray spectroscopy. The structure of fibers was examined by means of differential scanning calorimetry and wide-angle X-ray scattering. The ability of calcium pimelate supported on the surface of the graphene oxide to nucleate the β-form of polypropylene was revealed. A considerable amount of the β-form crystals was obtained in the gravity spun fibers. In the fibers taken at moderate and higher velocities the β-form disappeared. The structure of the fibers extruded with the additive was similar to the structure of the fibers extruded from neat polypropylene. At moderate velocities, the content of mesophase in the structure was high. At higher velocities, the crystalline structure built only from α-form crystals was obtained. The paper presents a discussion of the changes observed in the fiber structure in connection with polypropylene nucleation.